HAK WARIS ANAK LAKI-LAKI TERTUA DALAM HUKUM ADAT LAMPUNG PEPADUN PERSPEKTIF GENDER (STUDI DI TEGINENENG KABUPATEN PESAWARAN) - Habib Ismail; Hasyim Asy'ari; Agus Setiawan (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2019)
The existing Lampung Indigenous Peoples Pepadun in Tigeneneng sub-district, Kab. Pesawaran, adheres to a patrilneal kinship system. This means that the oldest son is an absolute heir in the implementation and management of inheritance with the highest customary title, namely balancing. Whereas for the female heirs, they were not given the right of authority in management, because in the adat of Lampung Province the daughters were considered unable to manage inheritance and daughters when they were married, so they would change their customary titles and would follow their husbands. This type of research is a field using a qualitative approach by analyzing data inductively. The result of this research is that the system applied in the distribution of inheritance rights to the eldest child in the Lampung tribal community, is clearly very contrary to the principle of gender equality and justice. Juridically normative equality and gender justice have been regulated in Islamic Law and International Convention (CEDAW). Even though juridically, girls have the same rights as boys in managing inheritance left by both parents.